Left ventricular dyssynchrony measured by cardiovascular magnetic resonance-feature tracking in anterior ST-elevation myocardial infarction: relationship with microvascular occlusion myocardial damage - Sun, Zheng; Wang, Yu; Hu, Yingying; Wu, Fang; Zhang, Nan; Liu, Zhi; Lu, Jie; Li, Kuncheng (Frontiers in Cardiovascular Medicine, 2023)
Objectives Cardiovascular magnetic resonance-feature tracking (CMR-FT) enables quantification of myocardial deformation and may be used as an objective measure of myocardial involvement in ST-elevation myocardial infarction (STEMI). We sought to investigate the associations between myocardial dyssynchrony parameters and myocardium damage for STEMI. Methods We analyzed 65 patients (45–80 years old) with anterior STEMI after primary percutaneous coronary intervention during 3–7 days [observational (STEMI) group] and 60 healthy volunteers [normal control (NC) group]. Myocardial dyssynchrony parameters were derived, including global and regional strain, radial rebound stretch and displacement, systolic septal time delay, and circumferential stretch. Results CMR characteristics, including morphologic parameters such as left ventricular ejection fraction (LVEF) (45.3% ± 8.2%) and myocardium damage in late gadolinium enhancement (LGE) (19.4% ± 4.7% LV), were assessed in the observation group. The global radial strain (GRS) and global longitudinal strain (GLS) substantially decreased in anterior STEMI compared with the NC group (GRS: 19.4% ± 5.1% vs. 24.8% ± 4.0%, P < 0.05; GLS: −10.1% ± 1.7% vs. −13.7% ± 1.0%, P < 0.05). Among 362 infarcted segments, radial and circumferential peak strains of the infarcted zone were the lowest (14.4% ± 3.2% and −10.7% ± 1.6%, respectively). The radial peak displacement of the infarct zone significantly decreased (2.6 ± 0.4 mm) (P < 0.001) and manifested in the circumferential displacement (3.5° ± 0.7°) in the STEMI group (P < 0.01). As microvascular occlusion (MVO) was additionally present, some strain parameters were significantly impaired in LGE+/MVO+ segments (radial strain [RS]: 12.2% ± 2.1%, circumferential strain [CS]: −9.6% ± 0.7%, longitudinal strain [LS]: −6.8% ± 1.0%) compared to LGE+/MVO− (RS: 14.6% ± 3.2%, CS: −10.8% ± 1.8%, LS: −9.2% ± 1.3%) (P < 0.05). When the extent of transmural myocardial infarction is greater than 75%, the parameter of the systolic septal delay (mean, 148 ms) was significantly reduced compared to fewer degrees of infarction (P < 0.01). Conclusion In anterior STEMI, the infarcted septum swings in a bimodal mode, and myocardial injury reduces the radial strain contractility. A more than 75% transmural degree was the septal strain-contraction reserve cut-off point.